MEDIATION BY PSYCHOLOGICAL DISTRESS IN THE ASSOCIATION BETWEEN BULLYING VICTIMIZATION AND SUICIDAL BEHAVIORS AMONG ADOLESCENTS - I Gusti Ngurah Edi Putra; Ni Nyoman Astri Artini (Jurnal Berkala Epidemiologi, 2022)
Background: Bullying victimization has been found to be associated with suicidal behaviors among adolescents. However, there is a lack of studies examining the mediating pathways. Purpose: This study aims to investigate psychological distress as a candidate mediator to the association between bullying victimization and suicidal behaviors. Methods: This was a cross-sectional study involving 10,883 records of school-going adolescents, retrieved from the 2015 Indonesia Global School-based Student Health Survey (IGSHS). The primary independent variable was the experience of being bullied in the last 30 days. In contrast, the dependent variable was any suicidal behaviors (i.e., suicidal ideation, planning, or attempt) reported in the last 12 months. Psychological distress as a candidate mediator was measured as loneliness, anxiety-induced sleep disturbance (in the past 12 months), and a combination of both measures – psychological distress. Causal mediation analysis with single mediation models was used to investigate the mediation using psychological distress measures by adjusting for potential confounders. Results: This study found conceivable pathways linking bullying victimization to suicidal behaviors through all measures of psychological distress with statistically significant Natural Indirect Effect (NIE): loneliness (aOR=1.17; 95%CI=1.11-1.27), anxiety-induced sleep disturbance (aOR=1.16; 95%CI=1.10-1.27), and psychological distress (aOR=1.21; 95%CI=1.15-1.31). The proportions mediated by loneliness, anxiety-induced sleep disturbance, and psychological distress accounted for 24.58%, 23.03%, 29.27%, respectively. Findings also suggest that the mediation by all measures of psychological distress persisted among both genders, with higher proportions mediated reported among boys. Conclusion: Psychological distress mediated the associations between bullying victimization and suicidal behaviors among Indonesian adolescents.